(untitled) (Proceedings of Southern Federal University. Philology, 2014)
The article deals with the analysis of modern state of the Ukrainian journalism study. The author suggests that modification of the paradigm of journalism study research is prepared by the logic of scientific and social development of Ukraine in the late 20th century. The main problems which emerged in the Ukrainian journalism study in connection with the transition to a platform of social communications are examined. The tasks that need to be solved by the Ukrainian scientists for proper organization journalism study research in a new scientific direction are determined. Keywords: Ukrainian journalism study, socially communication scientific paradigm, media research, social communications. Author: Orlova N. V.